The value of radiotherapy in control of locoregional recurrence breast cancer - Torres, Miguel; Santini, Alejandro (Cirugía del Uruguay, 1996)
On the basis of retrospectiva survey of 250 patients with locorregional recurrence of mammary cancer the study undertaken determines their general characteristics, stress being laid on the results obtained by radiotherapy as we/1 as on the role accomplished by prognostic indicators. Further emphasis is placed on the need to indicate supplementary postoperative radiotherapy in the presence of unfavorable prognostic factors of locorregional recurrences